Analysis of the Determinants of Pelni Mobile Adoption Failure in Manokwari: A Hybrid Diffusion of Innovation and Theory of Planned Behaviour Approach - Bonai, Yubelina Meilia; Sumendap, Andreas Leonardo; Sanglise, Marlinda (Politeknik Negeri Batam, 2026)
The adoption of digital services like Pelni Mobile in developing regions faces complex challenges. Despite offering ease of access, its adoption rate in Manokwari Regency remains low. Previous studies have not extensively explored typical barriers such as resistance to change, perceived financial costs, inconvenience, and ease of access. This study analyzes the factors behind Pelni Mobile's adoption failure by integrating the DOI and TPB approaches. Data were collected via online questionnaires from 435 participants and analyzed using SEM-PLS. Findings show that Perceived Financial Cost (P=0.000), Resistance to Change (P=0.000), and Inconvenience (P=0.000) have a significant negative influence on Behavioral Intention to Use. This means perceived costs, resistance to change, and inconvenience can reduce usage interest. Conversely, Perceived Ubiquity (P=0.000) has a significant positive influence on usage intention, and Behavioral Intention to Use positively influences Use Behavior, indicating that ease of access can encourage adoption.The implications highlight the need for strategies to reduce financial barriers, improve accessibility, employ educational approaches to address resistance, and enhance user experience. For developers and policymakers, these results serve as a guide for designing more inclusive digital services tailored to the characteristics of developing communities, particularly in contexts similar to Manokwari. Generalizing the findings to other regions must consider local social, economic, and cultural differences.